The association of NLR and MPV with treatment responses, disease stages, and international prognostic index scores in diffuse large B-cell lymphoma - Demircioğlu, Sinan; Doğan, Ali; Ekinci, Ömer; Demir, Cengiz (Yuzuncu Yil Universitesi Tip Fakultesi, 2019)
Diffuse Large B-Cell Lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma. International Prognostic Index (IPI) is the most commonly used scoring system predicting the prognosis. In this study, we aimed to investigate the association of Neutrophil/Lymphocyte Ratio (NLR) and Mean Platelet Volume (MPV) with IPI score, treatment responses, and disease stage. A total of 113 DLBCL patients who received R-CHOP treatment were recruited for this study. Demographic data, disease stages according to the Ann Arbor staging system, IPI scores, treatment methods, treatment responses, complete blood counts, and biochemical tests of the patients were retrospectively evaluated. Elevated NLR had statistically significant correlation with disease stage and IPI score (p=0.001 and p=0.006, respectively). However, the NLR had no statistically significant correlation with the interim-treatment and post-treatment responses (p=0.187, and p=0.96, respectively). MPV showed no significant relationship with disease stages (p=0.56), IPI scores (p=0.188), interim-treatment and post-treatment responses (p=0.122, and p=0.239). In conclusion, NLR was associated with IPI score and disease stage. This suggests that NLR, a cheap and easy investigation, may be used to obtain information about the prognosis. © 2019, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Diffuse large B-cell lymphoma; Mean platelet volume; Neutrophil/Lymphocyte ratio; Prognosis